2017
DOI: 10.3390/ijms18112395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Labile Zinc on Heart Function: From Physiology to Pathophysiology

Abstract: Zinc plays an important role in biological systems as bound and histochemically reactive labile Zn2+. Although Zn2+ concentration is in the nM range in cardiomyocytes at rest and increases dramatically under stimulation, very little is known about precise mechanisms controlling the intracellular distribution of Zn2+ and its variations during cardiac function. Recent studies are focused on molecular and cellular aspects of labile Zn2+ and its homeostasis in mammalian cells and growing evidence clarified the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 173 publications
(300 reference statements)
0
19
0
Order By: Relevance
“…The [Zn 2+ ] i -homeostasis and the suborganelle levels of [Zn 2+ ] are altered under pathological conditions, including hyperglycemia in cardiomyocytes [37,38]. Moreover, we have shown that a re-distribution of the expression level of some Zn 2+ -transporters can play an important contribution to those changes [37,39].…”
Section: Introductionmentioning
confidence: 99%
“…The [Zn 2+ ] i -homeostasis and the suborganelle levels of [Zn 2+ ] are altered under pathological conditions, including hyperglycemia in cardiomyocytes [37,38]. Moreover, we have shown that a re-distribution of the expression level of some Zn 2+ -transporters can play an important contribution to those changes [37,39].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found decreased Zn concentrations in HF patients, but there have also been reports where no significant differences were observed in terms of serum Zn levels between HF patients and the control group ( Kosar et al, 2006 ; Ghaemian et al, 2011 ; Alexanian et al, 2014 ; Salehifar et al, 2008 ; Shokrzadeh et al, 2009 ). Zn plays a major role in controlling cardiac contractility in cardiomyocytes, which may ultimately improve cardiac function ( Turan & Tuncay, 2017 ), hence maintaining normal Zn levels seems to serve a protective role in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed Ghaemian et al, 2011;Alexanian et al, 2014;Salehifar et al, 2008;Shokrzadeh et al, 2009). Zn plays a major role in controlling cardiac contractility in cardiomyocytes, which may ultimately improve cardiac function (Turan et al, 2017), hence maintaining normal Zn levels seems to serve a protective role in HF patients.…”
Section: Discussionmentioning
confidence: 99%